Influence of Economic Recession on Lifelong Education in Nigeria - Amoramo, John Davis; Okon, Glory James (International Journal of Educational Management, 2021)
The study examined the influence of economic recession on lifelong education in Nigeria. Ex-post-facto design was adopted for the research. Two hypotheses were formulated to guide the study. A 30-item questionnaire titled: Economic Recession and Lifelong Education in Nigeria Questionnaire (ERLENQ) was the instrument used for data collection, designed on a four-point Likert scale ranging from Strongly Agree (SA), Agree (A), Disagree (D), and Strongly Disagree (SD). The questionnaire was faced-validated by three experts: two from the Department of Educational Foundations and Child Education and one from the Department of Business Education, all of Cross River University of Technology, Calabar. A pilot test of the instrument was done and Cronbach Alpha reliability coefficients of 0.88, 0.79 and 0.82 were obtained. The questionnaire was administered on 1,200 teachers drawn from all public higher educational institutions in 12 sampled states. Stratified random sampling techniques was used in selecting the respondents. The data obtained was analyzed using Simple Linear Regression tested at .05 level of significance with the aid of Statistical Package for Social Sciences (SPSS) version 20. Findings of the study showed that reduction in educational budget significantly influence lifelong education in Nigeria (F = 152869.053, p = .000 < .05) and there is significant negative influence of poor service condition of teachers on lifelong education in Nigeria (F = 10191.751, p = .000 < .05). Based on the findings of the study, recommendations were made to the effect that the Nigerian budgetary allocation to the educational sector should be increased and teachers' conditions of service be improved as a way of boosting lifelong education in Nigeria.